Challenges in Improving Customer Focus in Small-Sized House-building Companies in Brazil - Formoso, Carlos T.; Jobim, Margaret S.S. (Penerbit Universiti Sains Malaysia, 2006)
Some important changes in the business environment in several countries are forcing house-building companies to change their competitive strategies. This paper discusses a set of customer servicing practices, which have been adopted by small-sized house-building companies in Brazil that have been involved in quality management improvement programs, emphasizing customer satisfaction measurement. Such practices are referred to a model of the customer servicing process that integrates the main customer-interaction functions from product inception to building operation. Based on multiple case studies and also on a literature review, the main difficulties faced by this sector in terms of improving customer satisfaction are discussed and some improvement opportunities are pointed out.